Jietacin Derivative Inhibits TNF-α-Mediated Inflammatory Cytokines Production via Suppression of the NF-κB Pathway in Synovial Cells - Kyoko Muneshige; Yuki Inahashi; Makoto Itakura; Masato Iwatsuki; Tomoyasu Hirose; Gen Inoue; Masashi Takaso; Toshiaki Sunazuka; Yoshihisa Ohashi; Etsuro Ohta; Kentaro Uchida (MDPI AG, 2022)
Synovial inflammation plays a central role in joint destruction and pain in osteoarthritis (OA). The NF-κB pathway plays an important role in the inflammatory process and is activated in OA. A previous study reported that a jietacin derivative (JD), (Z)-2-(8-oxodec-9-yn-1-yl)-1-vinyldiazene 1-oxide, suppressed the nuclear translocation of NF-κB in a range of cancer cell lines. However, the effect of JD in synovial cells and the exact mechanism of JD as an NF-κB inhibitor remain to be determined. We investigated the effect of JD on TNF-α-induced inflammatory reaction in a synovial cell line, SW982 and human primary synovial fibroblasts (hPSFs). Additionally, we examined phosphorylated levels of p65 and p38 and expression of importin α3 and β1 using Western blotting. RNA-Seq analysis revealed that JD suppressed TNF-α-induced differential expression: among 204 genes significantly differentially expressed between vehicle and TNF-α-stimulated SW982 (183 upregulated and 21 downregulated) (FC ≥ 2, Q < 0.05), expression of 130 upregulated genes, including inflammatory cytokines (IL1A, IL1B, IL6, IL8) and chemokines (CCL2, CCL3, CCL5, CCL20, CXCL9, 10, 11), was decreased by JD treatment and that of 14 downregulated genes was increased. KEGG pathway analysis showed that DEGs were increased in the cytokine-cytokine receptor interaction, TNF signaling pathway, NF-κB signaling pathway, and rheumatoid arthritis. JD inhibited IL1B, IL6 and IL8 mRNA expression and IL-6 and IL-8 protein production in both SW982 and hPSFs. JD also suppressed p65 phosphorylation in both SW982 and hPSFs. In contrast, JD did not alter p38 phosphorylation. JD may inhibit TNF-α-mediated inflammatory cytokine production via suppression of p65 phosphorylation in both SW982 and hPSFs. Our results suggest that JD may have therapeutic potential for OA due to its anti-inflammatory action through selective suppression of the NF-κB pathway on synovial cells.